Development of microemulsions as a lubricant adittive in drilling fluid (Research, Society and Development, 2020)
The search for new formulations of lubricating additives in drilling fluids is constant, due to the need of the oil and gas industry to improve products and processes and preserve the ecosystem, contributing to the sustainable development. The use of microemulsions in the upstream phase is increasing, mainly in the area of advanced oil recovery, but innovative in the area of oil well drilling. The objective of this study was to develop and characterize biodegradable microemulsions and of low production costs for application as a lubricant additive for water-based drilling fluids. For this purpose, the following were carried out: a) stability test on microemulsions and additive drilling fluids; b) particle size testing in the microemulsions; c) turbidity point test, in order to evaluate the microemulsion behavior regarding temperature; and d) lubricity test of microemulsions, proposed lubricant and additive drilling fluids. The lubricity results found were satisfactory, showing that the microemulsified systems evaluated can be applied as biodegradable lubricant additives in water-based drilling fluids for oil well drilling, causing less environmental impact.